Les associations foncières pastorales : un dispositif de gouvernance concrète du foncier dans les territoires de montagne - Laurence Barthe; Corinne Eychenne (EchoGéo)
The pastoral land associations are tools of land restructuring created by the pastoral law of 1972 to propose a solution to the specific problems of the land in mountain (division, joint possessions, absentee owners). It is a very standardized statutory instrument, which nevertheless allows to implement original forms of governance thanks to three major elements: the (statutory) procedure which obliges, the object (the land) which involves and the scale (the municipality) which facilitates. Thus social and geographical closeness appears as the central ingredient which allows to explain the success of AFP.